Produksi Garam Dan Bittern Di Tambak Garam - Nur Taufiq-SPJ; Retno Hartati; Widianingsih Widianingsih (Universitas Diponegoro, 2016)
Rembang Regency could be named as Salt City because they have very high production after Pati Regency. Along the road of Juwana (Pati) - Rembang, salt pond could be seen as square salt sea equipped with windmill to take the sea water from the channel into the pond and is processed into salt. Although salt localproduction is sufficient enough for raw material of industry, therefore best practical technology it is needed. The objective of present work are to improve directly the process of salt production and basic technique for diversiificatio of salt production, i.e. salt and bittern. The result of present works as follows. Getrape type salt pond is applied, where young water embankment is located upstream and the down to seed pond 1, 2, 3, then distributed to cristalization pan. Seawater is taken through primary dykes to pump at elevation of 1.5 m, so still full of water during high tide. On cristalization pan (size of 200 m2) sea water will be settled during 7–10 days until its cristalized. Salt cristal was located under bittern solution could be scrap and collected in collection point. The left-after bittern of 29–30° Be could be flowed back into seed pan uo be collected in bitter collection point.